Wind energy in the built environment: a design analysis using CFD and wind tunnel modelling approach - Campos-Arriaga, Liliana (2009)
Renewable energies are a critical element for reducing greenhouse gases emissions and achieving a sustainable development. Until recently, building integration of renewable sources was focused on solar technologies. Nevertheless,building integrated wind turbines can and must be part of the solution to the global energy challenge.